2014
DOI: 10.1136/sextrans-2013-051467
|View full text |Cite
|
Sign up to set email alerts
|

Association betweenMycoplasma genitaliuminfection and HIV acquisition among female sex workers in Uganda: evidence from a nested case–control study

Abstract: ObjectivesCross-sectional studies have shown a strong association between Mycoplasma genitalium and HIV infections. We previously reported that in a cohort of female sex workers in Uganda, M genitalium infection at baseline was associated with HIV seroconversion. Here we examine the temporal association between the M genitalium infection status shortly before HIV seroconversion and HIV acquisition.MethodsA nested case-control study was conducted within a cohort of women at high risk for HIV in Kampala. Cases w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 18 publications
2
47
0
Order By: Relevance
“…genitalium infections reported here are similar to those reported previously in smaller studies of high-risk populations in the United States (6, 9, 10, 14, 15, 20) and in the European community (21, 22), Australia and New Zealand (2325), Asia (26, 27), and Africa (28, 29). Age-related trends for M.…”
Section: Discussionsupporting
confidence: 90%
“…genitalium infections reported here are similar to those reported previously in smaller studies of high-risk populations in the United States (6, 9, 10, 14, 15, 20) and in the European community (21, 22), Australia and New Zealand (2325), Asia (26, 27), and Africa (28, 29). Age-related trends for M.…”
Section: Discussionsupporting
confidence: 90%
“…Recent evidence has implicated the bacterium in clinically significant disease in females (2,3). Additional studies suggest that M. genitalium infection promotes HIV acquisition (4)(5)(6) and virus shedding (7,8). Moreover, in a recent meta-analysis, Lis et al (9) reported significant associations between M. genitalium infection and cervicitis, pelvic inflammatory disease, preterm birth, and spontaneous abortion.…”
mentioning
confidence: 99%
“…[15][16][17][18] M. genitalium infection in women may also be a co-factor in acquisition of HIV infection. 19 T. vaginalis is an important cause of NGU in Africa. In one study, it was the most common pathogen identified in urethral samples and found in 14% of symptomatic and 9% of asymptomatic men.…”
Section: Discussionmentioning
confidence: 99%